Participation on the indigenous cultural communities (ICCs) in Philippine politics emancipation or co-optation - Belano, Zoilo D., Jr. (2013)
The United Nations General Assembly initiated the International Decade of the World's Indigenous People as part of its program in increasing awareness and promoting the involvement and well-being of the indigenous peoples (IPs). Some countries heeded the call and have endeavoured to integrate them into the formal mainstream politics. Making them part of the political community and the significant political actors is indeed a noble initiative. However, the actual implementation or integration can very difficult tricky and challenging. This article expounds on the following legal frameworks which have paved the participation of indigenous cultural communities into Philippine politics have paved the participation of indigenous cultural communities into Philippine politics first, the inclusion of provisions on indigenous peoples in the 1987 Philippine Constitution; second, the creation of Cordillera Administrative Region (CAR) in Northern Philippines; third the enactment of the Indigenous People's Rights Act; and fourth, the legislation of the Local Government Code of 1991. The article then scrutinizes and evaluate whether or not their participation means their emancipation from or merely their co-optation with the existing government system. In addition, Sherry Ornstein's Ladder of Citizen's Participation is used to thoroughly evaluate in ICCs' participation. The evaluation shows that although said government initiative might be construed as emancipating the ICCs from being mere 'spectators' or underrepresented members of the society; the reality is that these efforts and mechanisms have been manipulatively utilized by the Philippine state just to co-opt and win them. These initiatives have not been well-motivated; hence, have not genuinely emancipated them.
Keywords: Indigenous peoples